Before-and-After Effects of Management Training on Psychological Safety, Job Satisfaction, and Client Satisfaction in Older Adult Daycare Facilities (International Journal of Physiotherapy, 2025)
Background: Psychological safety is the shared belief within a team that it is safe to take interpersonal risks. This concept has been associated with enhanced organizational outcomes, including higher job satisfaction, better employee performance, and greater customer satisfaction. Research shows that psychological safety enhances interprofessional collaboration, learning, and communication. Leadership, particularly among managers, plays a critical role in cultivating such an environment. The present study aimed to investigate the effects of psychological safety training for managers on employees’ psychological safety and job satisfaction, as well as client satisfaction, in older adult daycare facilities.Methods: Managers and manager candidates participated in monthly online training sessions that included lectures, discussions, and implementation of workplace initiatives focused on fostering open communication, addressing mistakes constructively, and leveraging employees’ strengths. Before and after the training, psychological safety, job satisfaction, and client satisfaction were assessed through anonymous questionnaires.Results: Statistical analyses revealed significant improvements in these three metrics following the training (p < 0.05). Key findings highlighted specific improvements (e.g., reduced fear of blame for mistakes, more precise job evaluation criteria) that contributed to enhanced employee satisfaction. Client satisfaction also improved significantly across all measures, suggesting that better employee interaction and communication were pivotal.Conclusion: Improved employee well-being positively influenced service quality, leading to higher client satisfaction. These findings underscore the importance of leadership in creating psychologically safe environments that enhance organizational and customer outcomes.